WAKAF REGULATIONS AND POLICIES BETWEEN INDONESIA AND MALAYSIA: COMPARISON AND IMPLICATIONS - Muhammad Amin Qodri; Rafiqi; Umar; Afi Parnawi (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the comparative regulation and implementation of waqf policies between Indonesia and Malaysia, focusing on the analysis of differences in the legal framework, asset management, legal certainty, transparency, technology adoption, resource support, and socialization and education. The main objective of this study is to understand the fundamental differences in waqf regulations and practices in the two countries and identify the implications of these differences on the effectiveness and efficiency of waqf management. Methods This study will use a normative legal approach with a comparative analysis approach. This method will involve several well-structured stages to ensure that the data obtained is valid, reliable, and relevant. The data used include laws and regulations, policy documents, and literature related to waqf in Indonesia and Malaysia. The results of the study show that Malaysia has advantages in terms of effective waqf asset management, better legal certainty, high transparency, and the adoption of sophisticated technology and innovation. In contrast, Indonesia faces challenges in terms of complex regulations, managerial capacity of nadzir, and limited technical and financial support. The implications of these findings point to the need for reform in the legal framework and increased capacity of nadzir in Indonesia. Adoption of technology and increased financial support and public education are also important to improve the effectiveness of waqf management in Indonesia. With these steps, it is hoped that waqf management can become more efficient, productive, and provide a greater positive impact on society.